As emoções de lidar com o envelhecer e a longevidade na saúde mental - Ferreira, Laryssa Dayanna Costa (Universidade Federal Rural do Semi-Árido, 2020)
This work comes from within the program Oficinando em Rede da Universidade Federal Rural do Semi-Árido, Mossoró/RN, which is dedicated to the study of paths for healing psychic suffering through actions that integrate different languages and technologies. The projects of the Mossoró/RN's Networking Workshop involve clients/users of mental health services, family members, professionals from multidisciplinary teams, students and researchers who participate in workshops as a way to enable free expression: arts – theater and painting, scenography, games and computer technologies. In this dissertation, we seek to broaden the understanding of the paths of aging and longevity in the context of clients served in a Center of Psychosocial Attention in Mossoró. The research we carried out is part of the following question: How do we deal with aging and longevity in the circumstances in which we seek mental health care and promotion? We currently have a significant increase in the rates that deal with the life expectancy of the population and the growth of the elderly population in the world, which also occurs in our country and in Mossoró. This growth is accompanied by the increase of requests for care in the Centers of Psychosocial Attention. In this scenario, we know that we are interacting with social-technical networks involved in social policies directed to the elderly: social rights such as retirement, protection, services; proposals and activities that change in the areas of health, culture, education, among others. In this research, we emphasize the necessary broadening of our understanding on how mental health promotion happens in the course of aging and the search for longevity, since the presence or absence of care in the psychic and collective dimensions that constitute human life interact with the networks that transform and may affect ways of living. As a theoretical network for the construction of understanding about the movements of cognition that present themselves as ways of dealing with aging and longevity, we seek support in the studies of Francisco Varela and Humberto Maturana (1995, 2001) and the explanations that these brilliant biologists give us about the conservation of life and the processes of knowing. The methodology that we adopt in the research is qualitative, in the form of intervention research that puts in first place the relationships in a shared doing, experience of a science that is done with others. The participating subjects were five clients of one of the Centers of Psychosocial Attention of Mossoró/RN, the CAPS II: Nurse Mariana Neumam Vidal da Costa that integrate the work in progress in the program Oficinando em Rede de Mossoró. Our methodological journey began in two stages. In the first one, I integrated myself in the workshops of the Network Workshop Program and in the planning meetings. During this period, I could observe the experience of the aging of the research subjects in the collective. In the second stage, we held workshops only with subjects/participants who experienced the circumstance of aging in their lives, this understanding was more attentive and related to each subject, from workshops and face-to-face meetings – before we began to live the serious crisis of the COVID-19 pandemic, when the meetings started to happen online. The cenopoesia, as an articulation of multiple languages and a mode of free expression of the human repertoires present in the workshops, enabled a collective construction and observation of productions in which each participant updated their ways of dealing with and understanding aging and longevity. As a result, of this research we were able to observe and understand each subject's ways of dealing with mental health in their pathways of aging and longevity. The life of this research provided a circular movement of actions and reflections that allowed us to visualize paths of possible changes and reconstruction of our life. We were able to distinguish some changes in the coordination of actions in language and in emotion: such as the adoption of practices of care, of strengthening, searches to cultivate joy and the power of living, through images in transformation, self-renewal of care, gestures and circumstances that invite us to take into our hands the very experience of living with care and attention to health
Keywords: Envelhecer; Longevidade; Oficinas; Saúde mental; Aging; Longevity; Workshops; Mental health; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES